Globalization and the Reconfiguration of the World Economic Order - Bucătar Diana Georgiana (Ovidius University Annals: Economic Sciences Series, 2018)
The world witnesses significant changes in the functioning of the global economic relations that gravitate around three major global players; this analytical contribution proposed a new systematization in the form of three possible perspectives, in the context of moving from a multilateral system, organized around one great power to a multipolar one, dominated by bilateral and regional arrangements. This article aimed to synthesize and logically structure the multitude of theories and ideas that revolve around the topic of reconfiguring the global economic order so that it becomes more accessible to a wider audience. We joined the economists concerned to decode where globalization is going, a mission that started decades ago but which remains one of the challenges of the 21st century. Thus, the elaboration of this paper involved an approach including several stages: documentation, information, synthesis and systematization, and finally, a personal approach on the world economic order.